Impacts of payments for environmental services on local development in northern Costa Rica: A fuzzy multi-criteria analysis - Locatelli, Bruno; Rojas, V.; Salinas, Z. (2008)
Market mechanisms for forest environmental services are increasingly used for promoting environmental conservation, and their impacts on development are of considerable interest. In Costa Rica a national scheme of Payment for Environmental Services (PSA) rewards landowners for the services provided by different forest land-uses. We evaluated the impacts of reforestation under the PSA on local development in the North of the country. We applied a fuzzy multi-criteria analysis including socioeconomic, institutional, and cultural dimensions and based on the individual perceptions of landowners. The impacts of the PSA applied to reforestation are positive; negative economic impacts are balanced by positive institutional and cultural impacts. In most dimensions, the impacts on the poorest landowners are notably positive and generally higher than for upper class landowners. However, the short-term incomes of the poorest landowners decrease as a consequence of reforestation. This problem may engender negative outcomes and reduce the participation of the poorest landowners in the PSA. Positive impacts were stronger for landowners applying to the PSAthrough a local non-governmental organization.